The heretical and erotic sparks of the performer Lia Garcia (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
In Cicatriz, performance presented at the 7th edition of the São Paulo International Theater Festival, held in March 2020, the performer, educator, poet, and Afro-Mexican activist Lia Garcia expresses the pain of being a trans* person, remembers victims of transfeminicide and mobilizes recurring elements in her work, such as affection, eroticism, and physical touch, like a collective cry of resistance. Cicatriz also reverberates the affections and dialogues that arose during the interaction with the Brazilian participants of her workshop Laboratory of Experimentation 1 - Disobedient Voices, offered during the same festival.
Keywords: Body; Eroticism; Trans identity; Performance; Transfeminism